Effects of artificial substratum types and exposure time on macroalgal colonization in a tropical stream - Branco, Ciro Cesar Zanini [UNESP]; Necchi, Orlando [UNESP]; Peres, Cleto K. [UNESP] (E Schweizerbart'sche Verlags, 2010)
This study examines the development of the macroalgal community in a tropical stream on different artificial substrata (material and surface texture) and over varying periods of time. Our study indicated that the physical structure of the substratum did not affect species richness, but did alter the abundance of the macroalgal community. In addition, our results suggested that the amount of surface roughness could be an important factor driving the development of the macroalgal communities. The presence of a mucilaginous matrix with many diatoms and algal propagules on the surface of the substrata may have accelerated the colonization process. Macroalgal abundance peaked after 21 days of exposure. Generally, macroalgal species richness increased during the study period, however, a reduction in species richness was observed after 105 days of exposure, probably, as a result of competitive interactions.
Keywords: Stream macroalgae; artificial substratum; exposure time; substratum types